On cooking : a textbook of culinary fundamentals - Labensky, Sarah R. (Prentice Hall, 1999)
Professionalism. Food safety and sanitation. Nutrition. Recipes and menus. Tools and equipment. Knife skills. Kitchen staples. Dairy products. Principles of cooking. Stocks and sauces...